Health professionals’ experiences of group-based cardiac telerehabilitation: A descriptive qualitative study - Renuka Julia Jacobsson; Päivi Kankkunen; Anne Oikarinen (Finnish Journal of eHealth and eWelfare)
It is estimated that 200 million people worldwide live with coronary artery disease (CAD). Secondary prevention for CAD patients is supported by strong evidence. Group-based cardiac telerehabilitation supervised by health professionals is a type of rehabilitation program that utilizes technologies to deliver rehabilitation services to many patients with CAD. This descriptive qualitative study aims to describe healthcare professionals’ experiences of group-based cardiac telerehabilitation. A purposive sample of healthcare professionals providing group-based cardiac telerehabilitation was interviewed (N=10) from October 2023 to January 2024. The interviews were audio-recorded, translated verbatim and analysed with inductive content analysis. The results were reported according to the Standards for Reporting Qualitative Research- guideline (SRQR). The analysis resulted in six main categories: professional practices and factors contributing to the practices, digital practices in telerehabilitation, manifestations of support in a group telerehabilitation, counselling on self-care engagement in telerehabilitation, manifestations of interaction in a group telerehabilitation and telerehabilitation as an enabler of follow-up care for patients with CAD. According to the health professionals’ experiences, telerehabilitation improves the availability of rehabilitation, creates opportunities for support and peer interactions among rehabilitees, and enhances the accessibility of coronary disease treatment and follow-up care. Given positive experiences, group-based cardiac rehabilitation should be further developed and its availability should be improved.